BID’AH DAN AL-TARK DALAM HUKUM ISLAM: SATU PENELITIAN AWAL: Bid’ah and al-Tark in Islamic Law: A Premilinary Study - Syed Jaafar, Syed Mohd Jeffri; Man, Saadan; Jamaludin, Mohd Hafiz (Jurnal Syariah, 2018)
The issue of bid’ah has been a subject of polemic amongst Muslims in Malaysia for a long time. Generally, there are two main schools in interpreting the meaning of bid’ah. Some scholars view that there are two sides of interpretation as to the meaning of bid’ah, namely hasanah and dalalah. While some other scholars are of the view that there is no place for bid’ah in Islamic law especially in matters pertaining to worship. These scholars are of the opinion that every bid’ah is dalalah. Bid’ah is literally defined as an act which never done by Prophet Muhammad SAW. In this context, it is similar with the meaning of al-tark. This paper attempts to explore and analyze the differences and similarities between the meaning of bid’ah and al-tark in Islamic law. The data collection of this qualitative study is mainly based on the library research. These data are deductively and inductively analyzed from selected examples. Among the findings of this study is that, there are significant differences between bidâ€˜ah and al-tark. Al-Tark is general in nature and it is not accepted as a source on Islamic law, while bid’ah dalalah is illegal and forbidden to be practised by Muslims.